Identity and society within ‘landscapes of memory’: Iron Age cult at Bronze Age ruins (1000-700 BC) - Adamson, C (2018)
In the aftermath of the Late Bronze Age ‘Collapse’ many Mycenaean and Minoan sites were left destroyed, abandoned, or diminished. In the Early Iron Age the vestiges of the Bronze Age at these sites formed ‘landscapes of memory’ in which communities engaged with the past through practices such as ‘tomb’ and ‘hero’ cult. An additional practice, to which previous scholarship has dedicated less attention, was cult practised at or amongst Bronze Age ruins. This thesis is a study of such cults in Crete, the Argolid, and Attica. In each case we explore the site’s development in the Bronze Age, through the ‘Collapse’, and during the Early Iron Age in order to recreate its ‘landscape of memory’ when cult activity was initiated. In turn we examine the finds, features, and practices of the cult itself. Thirteen instances of Iron Age cult at Bronze Age ruins are included. In Crete: Knossos, Amnisos, Phaistos, Agia Triada, Palaikastro, and Kommos. In the Argolid: Mycenae, Tiryns, Asine, Argos, and the Argive Heraion. In Attica: Athens and Eleusis. From this study it is argued that a cultic engagement with the Bronze Age past was an attractive prospect to Iron Age communities in Greece. The thesis uses the assembled evidence to make four particular claims: that Bronze Age ruins inspired a cultural memory of a glorious past represented in Homer and other oral tradition; that the commemoration of cultural memories fostered a common sense of identity; that in some communities cultural memories were a useful tool in the acquisition and consolidation of power; and that cultural memory was malleable, and ‘invented’ memories could be powerful in early Greece.